PROSES MANAJEMEN DALAM PRODUKSI SENI PERTUNJUKAN - Dadang Suganda (LP2M ISBI Bandung, 2016)
Production Management of Performing Arts is an activity to organize and coordinate the use of human, material, financial, and information resources. This activity is conducted effectively and efficiently to create and enlarge benefits for the performing arts produced. Management of thePerforming Arts can be considered as the process of achieving a variety ofresources to produce multipurpose performing arts. It is also the process ofreaching the goals and objectives of the organization, both commercially,socially, as well as potentially to maintain the existence of performance artitself.